2022
DOI: 10.3389/fpubh.2022.812268
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Polybrominated Diphenyl Ethers Concentrations in Human Placenta and Small for Gestational Age in Southwest China

Abstract: BackgroundPrenatal exposures to polybrominated diphenyl ethers (PBDEs) may affect fetal growth. Small for gestational age (SGA) is a measure based on birth weight and gestational age at birth and represents a good indicator of fetal growth but it has been used only in a small number of studies. The present study aimed to examine the associations between PBDEs exposure and the risk of SGA among participants from a birth cohort in Southwest China.MethodsThe concentrations of eight common PBDE congeners (BDE-28, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“… 56 , 58 PBDEs were also associated with other effects, such as growth delay in children. 62 In some cases, PBDE showed sex-specific effects. For example, PBDE maternal exposure was associated with behavioral issues in 12-y-old boys, but not in girls 63 ; prenatal exposure to PBDEs were inversely associated with shorter anogenital distance in boys.…”
Section: Discussionmentioning
confidence: 99%
“… 56 , 58 PBDEs were also associated with other effects, such as growth delay in children. 62 In some cases, PBDE showed sex-specific effects. For example, PBDE maternal exposure was associated with behavioral issues in 12-y-old boys, but not in girls 63 ; prenatal exposure to PBDEs were inversely associated with shorter anogenital distance in boys.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-1 is important for fetal growth and it was suggested that PBDEs are able to interfere with IGF-1 system secretion [ 162 , 163 , 164 ]. Epidemiological studies evaluated the correlation between PBDEs and BW, but results were discordant [ 165 , 166 , 167 , 168 , 169 ]. It was also reported that changes in placental DNA methylation might be part of the underlying biological pathway between prenatal PBDEs exposure and adverse fetal growth [ 170 ].…”
Section: Edcs and Endocrine Diseases—evidence In Humansmentioning
confidence: 99%
“…PBDEs suppress placental growth, possibly by increasing the production of reactive oxygen species and DNA methylation, which can mediate a restrictive growth environment for the foetus by reducing nutrient and hormone transport, resulting in foetal-growth-restricted infants [91][92][93]. The smaller placental size coupled with altered maternal thyroid hormones as an implication of exposure to PBDEs may be responsible for the lower birth weights observed in the studies in this review and other studies involving general populations [91,[94][95][96][97][98][99][100]. In addition, we identified two studies with a decline in other metrics used to estimate foetus development, such as abdominal circumference, femur length, and biparietal diameter in mothers with higher levels of PBDEs [99,101].…”
Section: Reproductive Healthmentioning
confidence: 99%